Comparison of Lung-Homing Receptor Expression and Activation Profiles on NK Cell and T Cell Subsets in COVID-19 and Influenza - Brownlie, Demi; Rødahl, Inga; Varnaite, Renata; Asgeirsson, Hilmir; Glans, Hedvig; Falck-Jones, Sara; Vangeti, Sindhu; Buggert, Marcus; Ljunggren, Hans-Gustaf; Michaëlsson, Jakob; Gredmark-Russ, Sara; Smed-Sörensen, Anna; et al. (Frontiers in Immunology, 2022)
Respiratory viral infections with SARS-CoV-2 and influenza viruses commonly induce a strong infiltration of immune cells into the human lung, with potential detrimental effects on the integrity of the lung tissue. Despite comprising the largest fractions of circulating lymphocytes in the lung, rather little is known about how peripheral blood natural killer (NK) cell and T cell subsets are equipped for lung-homing in COVID-19 and influenza. Here, we provide a detailed comparative analysis of NK cells and T cells in patients infected with SARS-CoV-2 or influenza virus, focusing on the protein and gene expression of chemokine receptors known to be involved in recruitment to the lung. For this, we used 28-colour flow cytometry as well as re-analysis of a publicly available single-cell RNA-seq dataset from bronchoalveolar lavage (BAL) fluid. Frequencies of NK cells and T cells expressing CXCR3, CXCR6, and CCR5 were altered in peripheral blood of COVID-19 and influenza patients, in line with increased transcript expression of CXCR3, CXCR6, and CCR5 and their respective ligands in BAL fluid. NK cells and T cells expressing lung-homing receptors displayed stronger phenotypic signs of activation compared to cells lacking lung-homing receptors, and activation was overall stronger in influenza compared to COVID-19. Together, our results indicate a role for CXCR3+, CXCR6+, and/or CCR5+ NK cells and T cells that potentially migrate to the lungs in moderate COVID-19 and influenza patients, identifying common targets for future therapeutic interventions in respiratory viral infections.